Insect masquerades. - Simon, Hilda (New York: Viking Press, 1968)
Surveys the many techniques and devices used by insects to trap prey or escape their enemies through camouflage or trickery.
Bibliography: p. [91]
Keywords: Insects -- -- Juvenile literature; Mimicry (Biology) -- -- Juvenile literature; Insects -- -- Habits and behavior; Camouflage (Biology)